Palliative care for Parkinson’s disease: suggestions from a council of patient and carepartners - Kirk Hall (Nature Portfolio, 2017)
Abstract In 2015, the Parkinson’s Disease Foundation sponsored the first international meeting on Palliative Care and Parkinson’s disease and the Patient Centered Outcomes Research Institute funded the first comparative effectiveness trial of palliative care for Parkinson’s disease. A council of Parkinson’s disease patients and carepartners was engaged to assist with both projects. This council wrote the following manuscript as an opinion piece addressed to the clinical and research community on how palliative care could be applied to people living with Parkinson’s disease and their families. The council endorses palliative care as an approach to the care of Parkinson’s disease patients and their families that seeks to reduce suffering through spiritual, psychosocial, and medical support. This approach should start at the time of diagnosis, as this is a very challenging time for patients and carepartners; includes better emotional support, educational resources, and closer follow-up than is currently standard; and continue through end-of-life care and bereavement.